Fuzzy n-normed linear space - AL. Narayanan; S. Vijayabalaji (International Journal of Mathematics and Mathematical Sciences)
The primary purpose of this paper is to introduce the notion of fuzzy n-normed linear space as a generalization of n-normed space. Ascending family of α-n-norms corresponding to fuzzy n-norm is introduced. Best approximation sets in α-n-norms are defined. We also provide some results on best approximation sets in α-n-normed space.